Percutaneous radiofrequency‐assisted liver partition versus portal vein embolization before hepatectomy for perihilar cholangiocarcinoma. Issue 1 (30th October 2019) - Melekhina, O.; Efanov, M.; Alikhanov, R.; Tsvirkun, V.; Kulezneva, Y.; Kazakov, I.; Vankovich, A.; Koroleva, A.; Khatkov, I.
Abstract : Background: Percutaneous radiofrequency‐assisted liver partition with portal vein embolization in staged liver resection (PRALPPS) represents an alternative to portal vein embolization (PVE) followed by major liver resection in patients with perihilar cholangiocarcinoma. Methods: This was an observational case–control study. Both procedures were applied in patients with a future liver remnant (FLR) volume of less than 40 per cent. The main end points of the study were short‐term morbidity and mortality for the two procedures. The study also compared the efficacy of the preresection phases estimated by kinetic growth rate (KGR), time interval and degree of hypertrophy of the FLR. Results: The first phase (preresection) was completed in 11 and 18 patients, and the second phase (resection) in nine and 14 patients, in the PRALPPS and PVE groups respectively. Major morbidity after the first stage did not differ between the groups. There were no differences in blood loss, severe morbidity or liver failure rate after the second stage, with no deaths. The mean KGR of the FLR after the preresection phase for PRALPPS was 3·8 (0·6–9·8) per cent/day, and that after PVE was 1·8 (0–6·7) per cent/day ( P  = 0·037). The mean time interval for FLR hypertrophy in the PRALPPS and PVE groups was 15 (6–29) and 20 (8–35) days respectively ( P  = 0·039). Conclusion: S hort‐term outcomes were similar for PRALPPS and PVE in terms of safety. Remnant hypertrophy was achieved more rapidly by PRALPPS. Abstract : Percutaneous radiofrequency‐assisted liver partition with portal vein embolization in staged liver resection (PRALPPS), modIfied ALPPS with reduced surgical trauma on the first stage, was used in 11 patients with perihilar cholangiocarcinoma. PRALPPS did not differ from portal vein embolization (PVE) in terms of morbidity or mortality. The kinetic growth rate and mean time interval for future liver remnant hypertrophy in the PRALPPS group were significantly better than those in the PVE group. Similar complication rates and outcomes Abstract : Antecedentes: La partición hepática asistida por radiofrecuencia percutánea con embolización de la vena porta en la resección hepática en varios tiempos quirúrgicos ( percutaneous radio‐frequency assisted liver partition with portal vein embolization in staged liver resection, PRALPPS) representa una alternativa a la embolización de la vena porta seguida de resección hepática mayor ( portal vein embolization, PVE) en pacientes con colangiocarcinoma perihiliar ( perihiliar cholangiocarcioma, PHCC). Métodos: Se trata de un estudio observacional de casos y controles. Se efectuaron ambos procedimientos en pacientes con un volumen hepático remanente futuro ( future liver remnant, FLR) < 40%. Los resultados principales del estudio fueron la morbilidad a corto plazo y la mortalidad de ambos procedimientos. En el estudio también se comparó la eficacia de las fases de pre‐resección mediante la tasa cinética de crecimiento ( kinetic growth rate, KGR), el intervalo de tiempo y el grado de hipertrofia del FLR. Resultados: Se completaron la primera (pre‐resección) y la segunda (resección) fase en 11/9 y 18/14 pacientes en los grupos PRALPPS y PVE, respectivamente. La morbilidad mayor tras el primer tiempo no difirió entre los grupos. No se observaron diferencias en la pérdida de sangre, morbilidad grave y tasa de insuficiencia hepática tras el segundo tiempo, sin que ocurriera ningún fallecimiento. La media de KGR del FLR tras la fase de pre‐resección fue de 3, 8 (0, 6‐9, 8) %/día en el grupo PRALPPS y de 1, 8 (0‐6, 7) %/día tras PVE ( P = 0, 037). La media de intervalo de tiempo de la hipertrofia del FLR en los grupos PRALPPS y PVE fue de 15 (6‐29) días y 20 (8‐35) días, respectivamente ( P = 0, 039). Conclusión: Los resultados a corto plazo fueron similares en términos de seguridad. La hipertrofia del hígado remanente se alcanzó más rápidamente con la PRALPPS.